Rival male relatedness does not affect ejaculate allocation as predicted by sperm competition theory. - Melissa L Thomas (Public Library of Science (PLoS), 2008)
When females are sexually promiscuous, the intensity of sperm competition for males depends on how many partners females mate with. To maximize fitness, males should adjust their copulatory investment in relation to this intensity. However, fitness costs associated with sperm competition may not only depend on how many males a female has mated with, but also how related rival males are. According to theoretical predictions, males should adjust their copulatory investment in response to the relatedness of their male rival, and transfer more sperm to females that have first mated with a non-sibling male than females that have mated to a related male. Here, for the first time, we empirically test this theory using the Australian field cricket Teleogryllus oceanicus. We expose male crickets to sperm competition from either a full sibling or non-sibling male, by using both the presence of a rival male and the rival male's actual competing ejaculate as cues. Contrary to predictions, we find that males do not adjust ejaculates in response to the relatedness of their male rival. Instead, males with both full-sibling and non-sibling rivals allocate sperm of similar quality to females. This lack of kin biased behaviour is independent of any potentially confounding effect of strong competition between close relatives; kin biased behaviour was absent irrespective of whether males were raised in full sibling or mixed relatedness groups.